Educational management and teacher job satisfaction in educational institutions of the Ayacucho region, Peru (Práxis Educativa, 2024)
Research on educational management and teacher job satisfaction is currently relevant because they are determining factors in the quality of education provided to students. The objective of the research was to establish the relationship between educational management and teacher job satisfaction in the Ayacucho region of Peru. The research was carried out on a sample of 374 teachers, obtained according to the stratified probabilistic sampling technique. The instrument used for data collection was the questionnaire on educational management and teacher job satisfaction. Likewise, it was carried out using a non-experimental, cross-sectional, correlational design. Spearman's Rho statistic was used for data processing, with a significance level of 0.05. The results found at the descriptive level show that 65.8% of teachers perceive educational management as good; on the other hand, 70.1% of teachers are satisfied with their teaching work. The hypothesis test obtained allows us to conclude at an inferential level that there is a significant relationship between educational management and teacher job satisfaction in educational institutions in the region of Ayacucho, Peru (rs=0.677, p=0.000